Theology's Responsibility and Tasks in Today's Church and World - Doré, Joseph (Theological studies, 2004)
[In this lecture, delivered originally at the Catholic University of America, Washington, the Archbishop of Strasbourg develops a question close to his heart, namely theology's responsibility and tasks in today's Church and world. After having enunciated as a principle the embeddedness of this responsibility in faith considered as a total entity, he then outlines the relationship between the different aspects of this faith and theology's multiple tasks. In the final section, he enumerates three formal characteristics of theology that emerge from its direct connection with faith.]